Al-ʿArūḍ wa al-Qāfiyah wa al-Qiyam al-Akhlāqiyyah fī Qaṣīdah "ʿAmadtu Ilayka Khayra al-Nāsi Ḥayyan" li al-Farazdaq - Desi Mulyasari; Akmaliyah Akmaliyah; Khomisah Khomisah (Dzil Majaz: Journal of Arabic Literature, 2026)
This study examines the prosodic structure and moral messages in the Qaṣīdah ʿAmadtu ʾIlayka Khayra al-Nāsi Ḥayyan by al-Farazdaq, a panegyric qaṣīdah (madḥ) consisting of 65 verses. Using a descriptive qualitative approach and library research method, this study applies ʿilm al-ʿarūḍ (metre), qawāfī (rhyme), and moral message theory for prosodic analysis and ethical value interpretation. The findings reveal that the qaṣīdah is composed in baḥr wāfir with a consistent base pattern of مُفَاعَلَتُنْ مُفَاعَلَتُنْ فَعُوْلُنْ  throughout all 65 verses. All positions of ʿarūḍ (end of the first hemistich) and ḍarb (end of the second hemistich) undergo ʿillat qatf (elision of the light cause and vowelling of the fifth consonant), while 53 verses undergo zihāf ʿaṣb (quiescence of the fifth vowelled consonant) in the ḥasyw (medial foot) position. The rawī (rhyme-determining letter) is mīm (م), classified as Muṭlaqah Mujarradah Mawṣūlah bil-Līn of the Mutawātir type. Moral message analysis identifies four categories of values: the human relationship with God, with oneself, with others, and with nature. These findings demonstrate that al-Farazdaq's prosodic mastery and moral depth are two mutually reinforcing dimensions that cannot be separated.